Purires and Picagres faults and its relationship with the 1990 Puriscal seismic sequence - Montero, Walter (2014)
New morphotectonic, structural, and seismological interpretations have allowed us to define the neotectonics of the region located between the northwestern border of the Talamanca cordillera and the southern flanks of Aguacate Mounts, along the central-western sector of the Central Costa Rican Deformed Belt. The principal tectonic structures identified in this study are the Purires, Zapote, Jaris, Bajos de Jorco and Picagres faults. They constitute a set of northwest dextral-slip faults, traversing for more than 45 km the previous mountains ranges. Transtensive and transpressive structures were identified along these faults. Another recognized structure is the Junquillo fault, a predominantly east-west sinistral fault that lies between the Purires and Picagres faults.The three stages of the 1990 Puriscal shallow seismic sequence are reviewed in this study and are related with some of the previous faults. The seismic activity began with a seismic swarm that showed a peak of activity between May and June. The swarm showed a migration of activity between the Picagres and Purires faults. A right-lateral surface fault rupture with a length of 400 m, associated with two seismic events occurred on June 8 (00:31 GMT; Md 4.8) and June 9 (00:34 GMT; Md 4.8), breaks a sector of the eastern branch of Charcón transtensive structure of the Picagres fault. The seismic sequence continued with the Barbacoas earthquake of June 30 (Ms 5.1). This earthquake and its aftershocks located until July 11, rupture a 9 km length segment of the Purires fault. Finally, the Piedras Negras earthquake of December 22, 1990 (Ms 5.7) and its aftershocks occurred until December 30, caused a rupture of 11 km length of the Picagres fault.